TEACHING READING COMPREHENSION OF NARRATIVE TEXT TO THE TENTH GRADE STUDENTS - Emi Br Bukit; Berlin Sibarani; Rika Rika (Universitas Negeri Medan, 2017)
This study aims at describing how the teachers teach reading comprehension of narrative text to the tenth grade students in Sibolangit and revealing the underlying reasons of why do they do that way. This study was conducted by using qualitative research design. The subject of this study were two english teachers who taught at tenth grade students of two SMA in Sibolangit they are : SMA Negeri 1 Sibolangit and SMA RK Deli Murni Bandar Baru in academic year 2016/ 2017. The data were analyzed by using Miles and Huberman data analysis technique. The technique of collecting the data was recorded from the classroom process in teaching reading comprehension of narrative text. The findings of the study show that most of teachers’ ways are not yet focusing on teaching reading comprehension but rather focusing teaching the knowledge of genre. The underlying reason of the teachers’ ways in teaching reading comprehension did not facilitate reading comprehension. It was due to the misperception of the concept of teaching reading comprehension. Keywords : Teaching,Reading Comprehension,Narrative Text.